New horizons in personality disorders—from neglect to necessity in geriatric care. - Voshaar, Richard C Oude; Dijk, Silvia D M van (Age & Ageing, 2025)
Personality disorders, characterised by enduring and maladaptive patterns of behaviour, cognition and emotional regulation, affect 1 in 10 older adults. Personality disorders are frequently encountered in geriatric care considering their association with multimorbidity and increased health care utilisation. Patients with personality disorders often receive inadequate somatic health care due to (i) difficulties in expressing their actual symptoms and needs, (ii) challenging interactions with professionals, and (iii) non-compliance with medical treatment and lifestyle advice. Acknowledging personality disorders in geriatric care may improve treatment outcomes of somatic diseases. Since empirical evidence on personality diagnosis and treatment in older adults is scarce, we summarise future endeavours. First, the development of age-inclusive diagnostic tools should be prioritised to ensure comparability across age groups and facilitate longitudinal research over the lifespan. Second, evidence-based treatment approaches should be tailored to older people. Insight-oriented psychotherapies remain effective in later life considering sufficient level of introspection. Supportive and mediative therapies may better suit those with significant cognitive or physical impairments. Geriatric care models should be ideal for managing the complex needs of these patients when a consistent approach can be assured within the geriatric team as well as within the network considering the high level of interdisciplinary exchange needed. Third, considering the dynamic nature of personality disorders older adults should not be excluded from studies using novel technologies for real-time monitoring and personalised care. By addressing these gaps, the field can improve somatic treatment outcomes and uphold the dignity and well-being of older adults with personality disorders.